PENGARUH DIABETES MELLITUS TERHADAP RESISTENSI ASPIRIN PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT BETHESDA YOGYAKARTA - Witasari, Hardi Astuti; Pinzon, Rizaldy Taslim; Kristin, Erna (Universitas Ahmad Dahlan, 2014)
The secondary prevention of ischemic stroke can be implemented by giving aspirin.However, some cases of aspirin resistance have been found. The purpose of this study was toexamine the influence of diabetes mellitus on the risk of aspirin resistance in ischemic strokepatients at Bethesda Hospital Yogyakarta. This study was using a nested case-control studydesign. The Cases group was subjects who resistance to aspirin therapy. The control group wassubjects who response to aspirin therapy. The factors that affect the incidence of aspirinresistance were analyzed by bivariate analysis chi square test. The proportion of diabetesmellitus in resistant group was bigger than the aspirin responsive group. Its odds ratio (OR) was1.605 (95% CI, 0.641 to 4.017) (p=0.155). Conclusion: Ischemic stroke patients at BethesdaHospital Yogyakarta with diabetes mellitus were not proved to have a bigger risk of aspirinresistance than the patients without diabetes mellitus.